Bibliometric Analysis of Cybersecurity Research Trends in Bangladeshi Educational Institutions (2020-2025) - Sharmin, Khadija (Journal of Information System and Informatics, 2025)
This study provides a bibliometric analysis of cybersecurity research in Bangladeshi educational institutions from 2020 to mid-2025. Using data from the Scopus database and tools like R and VOSviewer, the results show a steady increase in research output, from 23 publications in 2020 to 77 in 2024, with projections for continued growth in 2025. Key research areas include network security, machine learning, deep learning, and blockchain technologies. Rajshahi University of Engineering and Technology has been a leading institution, with Md. Alamgir Hossain (State University of Bangladesh) being a prominent contributor, publishing 15 articles and accumulating 358 citations. International collaborations have enhanced Bangladesh's global standing in cybersecurity. These findings highlight Bangladesh’s increasing role in cybersecurity research, with implications for addressing local challenges and strengthening national cybersecurity resilience.